Estimating European Temperature Trends - Knoblauch, Jeremias (Student Undergraduate Research E-journal!, 2015)
This paper presents estimates for common trends in European temperature panels using new estimators. The analyzed data contains 4000 Eurasian weather stations. A sampling algorithm robust against inherent geographical biases is developed, and appropriate estimators are evaluated. The estimations based on this evaluation show that commonalities in temperature movements disappear with growing geographical scope. They also reveal that European mean temperature increased by 1.8°C over the past 130 years, but estimates differ by region. A particularly pronounced increase has taken place since the 1980s. Further, a 20-year cycle is discovered, and a low-frequency fractal structure of temperature trends is proposed.